2018
DOI: 10.1111/psyg.12285
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the neural correlates of frontal lobe tests

Abstract: Background: The Executive Interview (EXIT25), the executive clock-drawing task (CLOX1), and the Frontal Assessment Battery (FAB) are used to assess executive function at the bedside. These tests assess distinct psychometric properties. The aim of this study was to examine differences in the neural correlates of the EXIT25, CLOX1, and FAB based on magnetic resonance imaging. Methods: Fifty-eight subjects (30 with Alzheimer's disease, 10 with mild cognitive impairment, and 18 healthy controls) participated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Of the 45 publications, which met inclusion criteria, one article was a review but not a systematic review, which is not included in the table, 30 articles proposed discrete lesion locations in the brain related to the CDT summarized in Table and Figure 2 . Nine articles examined the degree of white matter burden related to CDT (Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 45 publications, which met inclusion criteria, one article was a review but not a systematic review, which is not included in the table, 30 articles proposed discrete lesion locations in the brain related to the CDT summarized in Table and Figure 2 . Nine articles examined the degree of white matter burden related to CDT (Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…A previous systematic review reported the involvement of various brain regions in the performance of pre‐drawn CDT 18 . Some papers have highlighted the neurological correlation between CDT failure and the right inferior temporal gyrus, right superior temporal gyrus, and fusiform gyrus 13,15,16 . In severe AD, CDT performance depends on the function of the right hemisphere, especially the right inferior temporal gyrus, which is involved in the cortical processing of complex visual objects, including the face of a clock 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous structural imaging studies linked CDT performance to a number of unilateral and bilateral brain areas, including the frontal, parietal, temporal, occipital, and subcortical lobes 13‐16 . Age is suggested to have a negative correlation with the functions of the occipital and parietal lobes, which could contribute to poor CDT performance 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…80 Different studies are also targeting executive and frontal-lobe functioning in MCI, AD and healthy controls. [81][82][83] Authors of a multimodal MRI study in healthy adults showed that low deactivation of the DMN, high activation of the executive-control network and high WMH burden were the most accurate predictors of executive functioning at baseline. 82 In addition, greater AD pathology (assessed using CSF values), and poor WM structural connectivity within the DMN and the executive-control network predicted greater executive-dysfunction annual decline in asymptomatic subjects.…”
Section: Mri and Cognitionmentioning
confidence: 99%